Faktor Risiko yang Berhubungan dengan Stunting pada Balita Usia >6-59 Bulan di Wilayah Kerja Puskesmas Gunung Meriah - Erlian Damayani; Ramadhaniah Ramadhaniah; Vera Nazhira Arifin (Yayasan Literasi Sains Indonesia, 2025)
Stunting is a serious global problem affecting more than 160 million children under five worldwide. In Aceh Singkil, the stunting rate reached 34.01% (SKI, 2023). This study aims to determine the risk factors associated with stunting in toddlers aged >6–59 months in the Gunung Meriah Community Health Center, Aceh Singkil Regency, in 2025. This study used a descriptive analytical design with a cross-sectional approach. A sample of 98 respondents was selected randomly from the population of mothers with toddlers. Data collection was conducted through interviews and observations using questionnaires and measuring instruments, and analyzed using the chi-square test in the SPSS application. The results showed a stunting prevalence of 38.8%. Factors that had a significant relationship with stunting were complete basic immunization (p = 0.002) and exclusive breastfeeding (p = 0.002). Meanwhile, maternal knowledge, parenting patterns, and information sources did not show a significant relationship. The results of the multivariate analysis showed that immunization has a statistically significant relationship with the incidence of stunting, with a p-value of 0.002 and an OR of 3.846, meaning that toddlers who do not receive immunization have a 3.8 times greater risk of experiencing stunting compared to toddlers who receive complete immunizations. It was concluded that exclusive breastfeeding and complete immunization play an important role in preventing stunting. Therefore, it is recommended that the Health Office strengthen education regarding the importance of exclusive breastfeeding and immunization, as well as encourage parental involvement in monitoring children's growth and development.